PERANCANGAN UI/UX APLIKASI “DENGERIN” BERBASIS MOBILE MENGGUNAKAN METODE DESIGN THINKING - Mazaya, Nila Nazilatul; Suliswaningsih, Suliswaningsih (Komputa : Jurnal Ilmiah Komputer dan Informatika, 2023)
Changes in people's lifestyles are caused by the ease of use of technology, especially in the entertainment sector. In the field of entertainment, music is certainly no stranger to society, from children to parents. With digital advances and internet technology, music can be heard by millions of music lovers from all over the world. Music applications can increase interest and attract user attention to continue using them or diminish because they are bored using them. Problems that often occur when listening to music include not being user friendly, prices are quite expensive especially for students or students and also the services provided are less attractive. This study aims to find out how to increase user interest and keep it interesting using a music application. Therefore, the author tries to design a music application, namely the Dengerin Application. This design uses the Design Thinking method because it can produce creative solutions. In testing using a usability testing system with a score of 77,5. The result of this research is the design of mobile-based “Dengerin” application interface ehich was designed using figma.